Anterior mediastinal solid tumours in adults: characterisation using dynamic contrast-enhanced MRI, diffusion-weighted MRI, and FDG-PET/CT. Issue 11 (November 2015) - Yabuuchi, H.; Matsuo, Y.; Abe, K.; Baba, S.; Sunami, S.; Kamitani, T.; Yonezawa, M.; Yamasaki, Y.; Kawanami, S.; Nagao, M.; Okamoto, T.; Nakamura, K.; et al.
<x xml:space="preserve">Abstract</x> Aim To find significant parameters to characterise anterior mediastinal solid tumours in adults using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), diffusion-weighted MRI (DWI), and combined 2-[18F]-fluoro-2-deoxy-d-glucose positron-emission tomography/computed tomography (FDG-PET/CT). Materials and methods Forty-eight histologically confirmed anterior mediastinal solid tumours in 48 patients (24 men, 24 women; age range 21–83 years, mean 50.7 years) were examined. The parameters analysed were maximal diameter, presence of capsule/septa on T2-weighted images, time–signal intensity curves (TICs), apparent diffusion coefficient (ADC), and maximum standardised uptake value (SUVmax). Also examined was whether any differences between histological types could be seen in these parameters. In a validation study, 42 anterior mediastinal solid tumours in 42 patients were examined consecutively. Results The washout pattern on TIC was seen only in thymic epithelial tumours (20/32). SUVmax of lymphoma (mean, 17.9), malignant germ cell tumours (14.2), and thymic carcinomas (15.6) were significantly higher than that of thymomas (6.1). The mean maximal diameter of thymic epithelial tumours was significantly smaller than that of lymphomas (p<0.01) and malignant germ cell tumours (p<0.05). The validation study also yielded high accuracy (38/42, 91%) in differentiation among the anterior mediastinal solid tumours. Conclusion The SUVmax, TIC pattern on DCE-MRI, and maximal diameter might be useful to differentiate anterior mediastinal solid tumours in adults.